Electrical resistivity modulation of thermoelectric iron based nanocomposites. (November 2018) - Music, Denis; Schmidt, Paul; Czigány, Zsolt; Greczynski, Grzegorz; Geyer, Richard W.; Hans, Marcus
Abstract: Iron oxides are promising thermoelectrics, but their high electrical resistivity impedes broader applications. In this work, we have studied Fe oxides with metallic contributions. Pt and Ir additions are also considered to enhance the valence electron concentration and further modify the transport properties. Based on density functional theory explorations, Fe based clusters (Fe3, Fe4, and Fe3 Pt) are suggested to act as nucleation sites for metallic crystallites, while O leads to formation of an amorphous matrix. This has been validated by transmission electron microscopy and x-ray photoelectron spectroscopy of sputter-grown Fe-Pt-Ir-O thin films. Densely packed bcc Fe grains, approx. 2–3 nm in diameter, are embedded in an amorphous Fe-O matrix in the as-grown state. The Seebeck coefficient reaches even −411 μV K −1 and the electrical resistivity is up to 5 orders of magnitude lower than that of previously reported literature data on Fe oxides. We suggest that this peculiarity of our films is due to finite states localized at the Fermi level in these nanocomposites. Highlights: Iron oxides with metallic contributions were explored. Iron based clusters act as nucleation sites for bcc nanograins. Oxygen leads to formation of an amorphous matrix. The Seebeck coefficient reaches even −411 μV K −1 . Electrical resistivity is 5 orders of magnitude lower than literature values.